Influence of Environmental Variables on Corrosion of Carbon Steel - A.G., Gopalakrishna Pillai; K., Ravindran (Fishery Technology, 2025)
The influence of environmental variables on corrosion of carbon steel in Cochin Harbour waters was investigated. The ooeffidents of correlation between days of exposure and fouling, corrosion rate were worked out and polynominals for the same were determined. The ooeffldent of correlation between days of exposure and corrosion rate was signiflant at 0.1% level.